Spirituality as predictor of psychological well-being at work in the Moroccan context: A cross-sectional study - Mohamed MAKKAOUI; Fatima-Zahra HANNOUN; Khalid OUAZIZI; Amelia RIZZO; Driss AIT ALI; Abdelhalim CHERQUI; Kaoutar KHABBACHE; Murat YILDIRIM; Mahmood BAHRAMIZADEH; Sefa BULUT; Łukasz SZARPAK; Michal PRUC; et al. (Journal of Health and Social Sciences)
Introduction: The aim of this study was to analyze the relationship between spirituality at work and employees' psychological well-being in the Moroccan context. Methods: This cross-sectional, descriptive, and quantitative study involved a sample of 1,110 employees, of which 57.8% were men. Data were collected using an online questionnaire that included sociodemographic data, the “Spirituality at Work” scale, and the Psychological Well-being scale. Descriptive statistics and correlational analyses were utilized to analyse the data and investigate the research objectives of interest. Results: Our findings indicated a positive correlation between spirituality at work and well-being at work, with a significant impact indicated by a beta coefficient of 0.635 (p < 0.001). Among the dimensions of workplace spirituality, meaningful work emerged as a key predictor of well-being with a beta coefficient of 0.893. At the same time, a sense of community also showed a strong correlation with well-being at 0.724. The dimension of inner life had a moderate impact, reflected by a beta coefficient of 0.417. In terms of psychological well-being, dimensions such as autonomy (β = 0.363), positive relationships with others (β = 0.421), personal growth (β = 0.534), and purpose in life (β = 0.188) were all significantly associated, though purpose in life had the lowest correlation. Discussion: This study demonstrates that enhancing spirituality at work significantly contributes to employees' psychological well-being. Meaningful work and a strong sense of community are critical components of this relationship. The findings suggest that organizations should institutionalize spiritual values to foster a supportive and productive work environment, ultimately enhancing employee well-being and organizational effectiveness.